ASSOCIATION OF SERUM ADENOSINE DEAMINASE LEVELS WITH ACUTE KIDNEY INJURY IN DIABETIC PATIENTS - USMAN, M; SHAH, F (Biological and Clinical Sciences Research Journal, 2024)
Diabetes mellitus is a significant global health issue, and complications such as acute kidney injury (AKI) are prevalent in patients with type 2 diabetes. Serum adenosine deaminase (ADA) has been suggested as a potential biomarker for various metabolic conditions, including inflammation and kidney injury, but its association with diabetic kidney health remains understudied. Objective: To assess the association of serum adenosine deaminase (ADA) levels with acute kidney injury (AKI) in patients with type 2 diabetes. Methods: This observational comparative study was conducted at DHQ Teaching Hospital KDA, Kohat, from February 7, 2023, to August 7, 2023, following ethical approval. A total of 120 participants were enrolled, including 60 patients with type 2 diabetes and 60 non-diabetic controls. Laboratory investigations for both groups included serum ADA (U/L), HbA1c (%), and estimated glomerular filtration rate (eGFR) (mL/min/1.73 m²). Statistical comparisons between groups were made using appropriate tests, and correlations between serum ADA and other parameters were assessed. Results: The mean age of diabetic patients was 55.40 ± 8.29 years, and that of controls was 54.58 ± 21.64 years. The mean serum ADA level in diabetic patients was significantly higher at 43 ± 4.29 U/L compared to 16.32 ± 1.20 U/L in controls (p = 0.0001). Diabetic patients had a mean HbA1c of 8.30 ± 0.59%, significantly higher than that of controls (5.28 ± 0.59%) (p = 0.0001). The mean eGFR in diabetic patients was 82.61 ± 17.22 mL/min/1.73 m², lower than in controls (105.97 ± 12.07 mL/min/1.73 m²) (p = 0.0001). In diabetic patients, serum ADA levels were positively correlated with HbA1c (indicating poorer glycemic control) and negatively correlated with eGFR (suggesting declining kidney function). Conclusion: Elevated serum adenosine deaminase levels in type 2 diabetic patients are significantly associated with poor glycemic control and decreased kidney function. These findings indicate that serum ADA could serve as a potential biomarker for monitoring glycemic status and kidney health in diabetic patients at risk for acute kidney injury.